2017
DOI: 10.3390/app7060562
|View full text |Cite
|
Sign up to set email alerts
|

Damage Assessment Using Information Entropy of Individual Acoustic Emission Waveforms during Cyclic Fatigue Loading

Abstract: Featured Application: The work presented in this paper outlines three methods to analyze individual acoustic emission waves emitted within a cyclically-loaded metallic structure. Upon further development, one potential application of the proposed analysis methods would be to aid in estimating the remaining useful life of aircraft structures.Abstract: Information entropy measured from acoustic emission (AE) waveforms is shown to be an indicator of fatigue damage in a high-strength aluminum alloy. Three methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…With the recent advances in structural health monitoring (SHM) [2][3][4][5][6][7][8] and nondestructive evaluation (NDE) [9,10], many monitoring and evaluation methods, such as modal characteristics-based methods [11][12][13], active sensing [14][15][16][17][18][19][20], electromechanical impedance [21][22][23][24][25], ultrasonic guided wave [26], active thermography [26][27][28] and vibrothermography [29,30], among others, are available. Among them, acoustic emission technique [31][32][33][34][35][36][37] is an effective nondestructive technique that can characterize the wear process [38,39], and it has been widely used in civil engineering [40][41][42][43], mechanical engineering [44][45][46][47]<...>…”
Section: Introductionmentioning
confidence: 99%
“…With the recent advances in structural health monitoring (SHM) [2][3][4][5][6][7][8] and nondestructive evaluation (NDE) [9,10], many monitoring and evaluation methods, such as modal characteristics-based methods [11][12][13], active sensing [14][15][16][17][18][19][20], electromechanical impedance [21][22][23][24][25], ultrasonic guided wave [26], active thermography [26][27][28] and vibrothermography [29,30], among others, are available. Among them, acoustic emission technique [31][32][33][34][35][36][37] is an effective nondestructive technique that can characterize the wear process [38,39], and it has been widely used in civil engineering [40][41][42][43], mechanical engineering [44][45][46][47]<...>…”
Section: Introductionmentioning
confidence: 99%
“…Sauerbrunn et al [21] used Equation (3) to calculate information entropy using collected AE waveforms from many fatigue tests. In their research, the AE waveform was shown to be a more appropriate damage indicator than the traditional AE features, such as count and energy.…”
Section: Introductionmentioning
confidence: 99%
“…It has resulted in good agreement with the DEG theorem. Another approach has used acoustic energy dissipation during fatigue in the form of generated acoustic emission (AE) waveforms, where associated information entropy typically correlates well with the amount of the fatigue damage [21].Strain energy dissipation during the cyclic fatigue loading and unloading also appears to apply to the relative entropy. Crooks et al [22] have shown that the Kullback-Leibler divergence computed from loading/unloading distributions is equivalent to the thermodynamic entropy when distributions of loading/unloading processes are measurable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic loading and unloading tests with acoustic emission monitoring are an effective approach to quantitatively measuring deformation and damage characteristics of various materials [11][12][13][14][15][16][17][18][19][20]. Sherif et al [12] captured and analyzed AE signals to characterize the crack formation and crack width development in the cyclic loading processes.…”
Section: Introductionmentioning
confidence: 99%